2016
DOI: 10.1093/ajh/hpw001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Protective Effects ofMoringa oleiferaSeeds in Spontaneous Hypertensive Rats

Abstract: Our data show a beneficial effect of MOI on the cardiac structure and function in SHR associated with an upregulation of PPAR-α and δ signaling. This study thus provides scientific rational support for the empirical use of MOI in the traditional Malagasy medicine against cardiac diseases associated with blood pressure overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 37 publications
6
54
0
1
Order By: Relevance
“…The beneficial vascular effects observed in the present work are probably due to the presence in the seeds of tocopherols, phenolic acids (gallic and ferulic acids), and flavonoids (such as quercetin, catechin, and epicathechin) known for their potential antioxidant activity [34]. Moreover, we previously identified glucosinolates, in particular glucomoringin, in MOI seeds extract that can also contribute to its cardiovascular protective role [11]. Glucomoringin hydrolysis by myrosinase activity during food processing or digestion leads to the formation of isothiocianates (ITCs) [35].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The beneficial vascular effects observed in the present work are probably due to the presence in the seeds of tocopherols, phenolic acids (gallic and ferulic acids), and flavonoids (such as quercetin, catechin, and epicathechin) known for their potential antioxidant activity [34]. Moreover, we previously identified glucosinolates, in particular glucomoringin, in MOI seeds extract that can also contribute to its cardiovascular protective role [11]. Glucomoringin hydrolysis by myrosinase activity during food processing or digestion leads to the formation of isothiocianates (ITCs) [35].…”
Section: Discussionmentioning
confidence: 85%
“…Malagasy population employs MOI seeds against hypertension empirically, and in our previous study, we provided evidence of the cardiac protective role of a treatment with MOI seeds in spontaneously hypertensive rats (SHR) [11]. A physicochemical study suggested antioxidant properties of MOI seed oil [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a significant reduction in fibrosis in the left ventricle was also observed. However, treatment with M. oleifera seed powder did not modify blood pressure [68]. …”
Section: Phytochemistry and Medicinal Usesmentioning
confidence: 99%
“…An aqueous leaf extract from MO was reported to have lipid-lowering properties through reduction in the formation of cholesterol micelles and inhibition of pancreatic lipase, pancreatic cholesterol esterase, and bile acid binding [34]. In addition, upregulation of the expression of peroxisome proliferator-activated receptors (PPAR) α1 (PPARα1) and γ (PPARγ) has been observed in rats which received MO seed powder [55]. PPAR are crucial for lipid metabolism, ketogenesis, and cellular energetic homeostasis, and are expressed in several organs including liver, brain, muscle, and heart, among others.…”
Section: Mechanisms Of Action Of Momentioning
confidence: 99%